Treatment of Vascular Dementia by Using Fuyuan Capsule Combined with "Xingnao Kaiqiao" Acupuncture - LI Hongmei; WANG Xiaoqin; GUO Yang; SHI Hongxing; GUO Xiao; WANG Xue (康复学报)
ObjectiveTo observe the clinical effect of Fuyuan capsule combined with "Xingnao Kaiqiao" acupuncture on vascular dementia (VD) and explore its mechanism.MethodsA total of 150 VD patients with deficiency of spleen and kidney and blood stasis were enrolled in the Hengshui Traditional Chinese Medicine Hospital of Hebei Province from May 2020 to September 2021. According to the principle of 1∶1 random allocation, they were divided into treatment group and control group, with 75 cases in each group. The control group received "Xingnao Kaiqiao" acupuncture treatment and the treatment group received oral administration of Fuyuan capsule in addition to the treatment of the control group for 12 weeks. The mini-mental state examination (MMSE) score, modified Hasegawa dementia scale (HDS-R) score, and modified Barthel index (MBI) score were compared between the two groups before and after treatment; the levels of serum superoxide dismutase (SOD) and malondialdehyde (MDA) of patients before and after treatment were measured and analyzed by colorimetry. The expression of protein interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α) before and after treatment were determined by enzyme-linked immunoassay. Improvement in MMSE score was used as an index to assess the total effective rate in the two groups after treatment. Pearson correlation analysis was used to explore the correlation between MMSE score difference and changes of blood index levels before and after treatment.ResultsThe MMSE, HDS-R and MBI scores of both groups improved after treatment (P<0.05), those of the treatment group improved more, and the differences was statistically significant (P<0.05). After treatment, SOD activity increased, and MDA content, expression of protein IL-6 and TNF-α decreased in the two groups (P<0.05). Compared with the control group, SOD activity in the treatment group was higher, MDA content and expression of protein IL-6 and TNF-α were lower (P<0.05). The total effective rate of the treatment group (82.19%) was significantly better than that of the control group (68.06%) (P<0.05). The change of MMSE score was positively correlated with the change of SOD activity (r=0.520, P=0.003) and negatively correlated with the expression of TNF-α protein (r=-0.308, P=0.026).ConclusionFuyuan capsule combined with "Xingnao Kaiqiao" acupuncture could effectively improve the cognitive function of VD patients, improve the symptoms of vascular dementia and improve the ability of daily living activities, which may be related to relieving oxidative stress injury and inhibiting inflammatory response.